Clinical Association and Detection of Cervical Cancer with Pap Smear Screening Test - Hina Pirzada, Farheen Fatima, Seema Rafiq, Sadia Habib, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the clinical association of the cervical cancer with pap smear test. Study Design: Prospective study Place and Duration of Study: Department of Obstetrics & Gynaecology, AJK Medical College Muzaffarbad Azad Kashmir from 1st January 2021 to 30th June 2022. Methodology: Five hundred women were screened who were between 20-55 years of age. Sampling was performed by ecto-cervix through wooden Ayre spatula rotation at 360 degrees. The sample was preserved in a formalin jar and sent for glass slide formation. Cytopathological examination presented lesions as negative intraepithelial neoplasia as well as epithelial-cell abnormalities including squamous in addition to glandular cells. Results: The mean age was 41.5±5.6 years. The epithelial abnormalities were diagnosed in 6% of low grade squamous-intraepithelial lesion cases and 1% in high grade squamous intra-epithelial lesion through pap smear. No case of squamous cell carcinoma was identified while 40% showed inflammation presence Most of the females within 31-40 years were having normal cervical morphology while 36%cases inflammation was noticed in 21-30 years of age. Low grade squamous-intraepithelial lesion was noticed in 63.3% of the women within an age group of 14-50 years while high grade squamous intra-epithelial lesion L was observed within 60% of the similar age women. Majority (148.45%) of the women had white discharge from vaginum followed by cervical erosion seen in 19.21% of the cases Conclusion: Pap smear is a highly specific and efficient test for determining pre-cancerous cervical lesions as well as cervical cancers. Key words: Association, Detection, Cervical cancer Pap smear screening test